PENDEKATAN STUDI KEBIJAKAN PENDIDIKAN ISLAM - Isyatir Radiah (AN-NUR: Jurnal Pendidikan dan Pembelajaran, 2026)
Islamic education plays a strategic role in shaping the character and civilization of the people, thus requiring comprehensive review of policies governing it. The study of Islamic education policy is not merely technical-administrative but also contains strong normative, philosophical, and social dimensions. This article aims to analyze the main approaches in the study of Islamic education policy and their relevance to the formulation and implementation of Islamic education policy in Indonesia. This study uses a qualitative approach with library research. Data were obtained from books, journal articles, and relevant policy documents, then analyzed using descriptive-analytical techniques through the stages of collection, classification, interpretation, and drawing conclusions. The results of the study indicate that Islamic education policy requires an integrative approach encompassing religious, social, philosophical, epistemological, and pedagogical approaches. Public policy models also play a crucial role in bridging the ideal values ​​of Islam with the reality of policy implementation. In conclusion, an effective Islamic education policy is one that is grounded in Islamic values, responsive to social dynamics, and capable of integrating spiritual, intellectual, and moral aspects into the educational process.